Optimizing Students’ Arabic Writing Skills through Project-Based Learning Based on Digital Storytelling - Kholida Nur; Ahmad Mubaidilah; Suhono Suhono (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to examine the implementation of Project-Based Learning (PJBL) integrated with digital storytelling to develop students’ Arabic writing skills (Mahārah Kitābah). The study employed a descriptive qualitative approach and was conducted with third-semester students of the Arabic Language Education Program at Universitas Ma’arif Lampung. Data were collected through classroom observations, semi-structured interviews, documentation, and analysis of students’ digital storytelling projects. The findings indicate that the integration of digital storytelling into PJBL supported the development of students’ ability to compose Arabic narrative texts in a more structured, communicative, and contextual manner. The project-based activities also increased students’ engagement and motivation to write by providing opportunities to produce authentic texts and publish their work through digital and social media platforms. Furthermore, the learning model facilitated the development of several 21st-century competencies, particularly digital literacy, creativity, collaboration, and communication. These findings suggest that the integration of digital storytelling into PJBL can serve as an innovative learning strategy for developing students’ Mahārah Kitābah in Arabic language education, particularly in response to the demands of digital learning environments